A sheathless high precise particle separation chip integrated contraction–expansion channel and deterministic lateral displacement. (13th February 2023) - Li, Xiaohong; Duan, Junping; Wang, Jiayun; Qu, Zeng; Zhang, BinZhen
Abstract: Cell sorting plays an important role in medical and biological research. This study aimed to propose a novel approach combining a contraction–expansion array (CEA) channel and a deterministic lateral displacement (DLD) array to achieve high-throughput and high-precision particle separation of different sizes. The CEA channel could realize the focusing and preliminary sorting of particles with different sizes under the joint action of inertia force and Dean resistance. The separation purity and efficiency could be further improved by coupling triangular microcolumn DLD. The finite element simulation analysis was carried out using commercial software COMSOL Multiphysics 5.4. The flow field distribution and the particle movement trajectory under the CEA channel and DLD array were simulated, respectively. The simulation results showed that this structure could achieve high-throughput and high-precision particle separation of different sizes. Finally, the separation experiments showed that the separation efficiency of 5 µ m polystyrene microspheres as the target particles was more than 99%, and the separation purity was 96.1% under a high flow velocity. The microfluidic chip had the advantages of low cost, simple preparation process, and label-free, sheathless characteristics, thus realizing high-efficiency, high-throughput particle separation of different sizes. In general, the proposed approach provided a new pathway for sheathless particle separation with high precision and high throughput.